2014
DOI: 10.1111/add.12466
|View full text |Cite
|
Sign up to set email alerts
|

Personal tobacco pack display before and after the introduction of plain packaging with larger pictorial health warnings in Australia: an observational study of outdoor café strips

Abstract: Following Australia's 2012 policy of plain packaging and larger pictorial health warnings on cigarette and tobacco packs, smoking in outdoor areas of cafés, restaurants and bars and personal pack display (packs clearly visible on tables) declined. Further, a small proportion of smokers took steps to conceal packs that would otherwise be visible. Both are promising outcomes to minimize exposure to tobacco promotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 30 publications
5
51
1
1
Order By: Relevance
“…Since 2017, tobacco products sold in the UK similarly have standardized green packaging with graphic health warnings covering at least 65% of the front and back of the pack. Although the implementation of plain cigarette packaging has been debated, initial studies suggest that the implementation of plain packaging regulations in Australia has been effective in changing consumers' smoking behavior, resulting in a smallto-medium sized reduction in smoking prevalence (Zacher et al 2014). The implementation of the plain packaging regulation further correlates with a decline in the prevalence of active smoking and with a reduction in the number of cigarette packets openly displayed by consumers in cafes, restaurants, and bars (Zacher et al 2014).…”
Section: Removing or Reducing Exposure To Situational Cues That Activmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2017, tobacco products sold in the UK similarly have standardized green packaging with graphic health warnings covering at least 65% of the front and back of the pack. Although the implementation of plain cigarette packaging has been debated, initial studies suggest that the implementation of plain packaging regulations in Australia has been effective in changing consumers' smoking behavior, resulting in a smallto-medium sized reduction in smoking prevalence (Zacher et al 2014). The implementation of the plain packaging regulation further correlates with a decline in the prevalence of active smoking and with a reduction in the number of cigarette packets openly displayed by consumers in cafes, restaurants, and bars (Zacher et al 2014).…”
Section: Removing or Reducing Exposure To Situational Cues That Activmentioning
confidence: 99%
“…Although the implementation of plain cigarette packaging has been debated, initial studies suggest that the implementation of plain packaging regulations in Australia has been effective in changing consumers' smoking behavior, resulting in a smallto-medium sized reduction in smoking prevalence (Zacher et al 2014). The implementation of the plain packaging regulation further correlates with a decline in the prevalence of active smoking and with a reduction in the number of cigarette packets openly displayed by consumers in cafes, restaurants, and bars (Zacher et al 2014). Laboratory research also shows that, relative to branded packaging, plain cigarette packaging reduces motivation to purchase cigarettes (Brose et al 2014), self-reported engagement in smoking (Moodie et al 2011;Moodie and Mackintosh 2013), the likelihood of accepting a packet of cigarettes (Hammond, Daniel, and White 2013), and engagement in tobacco-seeking behavior .…”
Section: Removing or Reducing Exposure To Situational Cues That Activmentioning
confidence: 99%
“…In the group called -tuxedo‖, Zacher et al (2014) also discussed the issue of information and warnings on cigarette packages. In the cluster -U.S. taste market‖, cigarettes again became an object of study.…”
Section: Figure 5 Network Between Countriesmentioning
confidence: 99%
“…Following the provision of WHO-FCTC, Australia introduced legislation for GHW and plain tobacco packaging that has resulted in a significant reduction in personal pack display and smoking rates on outdoor areas of cafes, restaurants and bars (9). Also, the number of smokers agreeing that their pack is attractive, appealing and fashionable significantly has decreased over time (10).…”
mentioning
confidence: 99%